Conceptualizing Digital Awareness: Introducing a Definition via a Scoping Review of Digital Literacy and Digital Citizenship - Brummer, Leonie (Innovations in Pedagogy and Technology, 2025)
Individuals need to be sufficiently digitally literate to (success)fully participate in our society due to the increased mediation and redefinition by digital technologies. Full participation in contemporary society requires an individual to be digitally aware. Serving as both a precursor and a successor, digital awareness will become increasingly prevalent in education. However, no clear definition has been derived in scholarship yet, contributing to ambiguity in society and education. Grounded in a scoping review of empirical research in the last nine years, 112 articles were included. By separating scholarship on digital literacy, digital citizenship and a combination of the aforementioned, this review displayed different foci on indications for awareness (e.g., a future link, its potential, and a comparison of, for example, the use of digital technologies). The current review conceptualizes digital awareness as an precursor and successor of digital literacy and citizenship—resulting in a conceptualization of digital awareness as “the degree to which an individual is able to critically recognize and reflect upon the declarative, structural, procedural, and conditional knowledge and understanding which are necessary to identify the necessities, opportunities, risks and consequences of the use of (future) digital technologies in and across an individual’s public, work, and private lives”. Conceptualizing digital awareness informs education (and policy) by contributing to conceptual coherence—as a precursor and successor of digital literacy and digital citizenship—and by directing learning objectives related to digital awareness, literacy and citizenship to allow individuals to become digitally literate for (success)full participation in society and education.